PELAKSANAAN GAME SCATTERGORIES DALAM PEMBELAJARAN KOSAKATA BAHASA ARAB - Opier, Ulfa Mawaddah Ahmad (STIQ Amuntai, 2023)
Learning with games is an exciting thing that encourages student interest because learning becomes interactive and can increase student motivation and interest. One form of game for learning foreign languages is game scattergories. This scattergories game was implemented at Islamic Senior high school 1 Malang to learn Arabic vocabulary. This research is a descriptive qualitative method that describes the process of learning Arabic vocabulary by using scattergories game in Islamic Senior high school 1 Malang and the advantages and disadvantages of applying the game process. In this research, participant observation, in-depth interviews, and documentation are data collection techniques—observation regarding learning Arabic vocabulary with the scattergories game. In-depth interview were conducted by interviewing Arabic teacher and students of class X-G of Islamic senior high school 1 Malang. The analysis technique adopts the Miles and Huberman model: data reduction, presentation, and conclusion. The research showed that: 1) There were six stages in learning Arabic vocabulary with scattergories at Senior High school 1 Malang, namely opening the lesson, dividing into groups, preparing and discussing, implementing the game, determining the winner and closing the lesson. 2) Learning with scattergories can increase motivation and encourage students to learn; students can think quickly and become the focus of learning. However, during the process, the teacher must make careful preparations, which require a relatively long time. The application of this game is fun and provides positive benefits for students.